Analisis Usahatani Bengkuang (Pachirizius erosus) di Kelurahan Situgede Kota Bogor - Pradya Paramitha Putri Asmoro; Ninuk Purnaningsih (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
The study was conducted in the Situgede Village with sources as the Saluyu I Farmers' Women's Group (KWT) in RW 01, Situgede Village, West Bogor District, Bogor City, West Java. Situgede Village is one of the yam bean central production in the City of Bogor, West Java. Yam bean (Pachyrhizus erosus L.) is a horticultural commodity whose economic value derived from tropical America and has light brown skin and fruit flesh that is close to white. Yam bean plant grows well in hot areas in humid environments and full of sun. This plant usually propagated by using seeds. This study aims to determine the effect of factors production (land area, labor, and cultivation input) on yam bean farming income and determine the income of yam bean farming. The method used in this research is structured interview method and R / C Ratio. The analysis showed that value of the R/C ratio is 1.8. The result showed yam bean farming at Saluyu I Farmers’ Women’s Group (KWT) profitable and economically feasible. Key words: Analysis, farming, yam bean